Peripheral blood transcriptome profiling enables monitoring disease progression in dystrophic mice and patients - Mirko Signorelli; Mitra Ebrahimpoor; Olga Veth; Kristina Hettne; Nisha Verwey; Raquel García‐Rodríguez; Christa L Tanganyika‐deWinter; Luz B Lopez Hernandez; Rosa Escobar Cedillo; Benjamín Gómez Díaz; Olafur T Magnusson; Hailiang Mei; et al. (EMBO Molecular Medicine, 2021)
Abstract DMD is a rare disorder characterized by progressive muscle degeneration and premature death. Therapy development is delayed by difficulties to monitor efficacy non‐invasively in clinical trials. In this study, we used RNA‐sequencing to describe the pathophysiological changes in skeletal muscle of 3 dystrophic mouse models. We show how dystrophic changes in muscle are reflected in blood by analyzing paired muscle and blood samples. Analysis of repeated blood measurements followed the dystrophic signature at five equally spaced time points over a period of seven months. Treatment with two antisense drugs harboring different levels of dystrophin recovery identified genes associated with safety and efficacy. Evaluation of the blood gene expression in a cohort of DMD patients enabled the comparison between preclinical models and patients, and the identification of genes associated with physical performance, treatment with corticosteroids and body measures. The presented results provide evidence that blood RNA‐sequencing can serve as a tool to evaluate disease progression in dystrophic mice and patients, as well as to monitor response to (dystrophin‐restoring) therapies in preclinical drug development and in clinical trials.